2010
DOI: 10.1016/j.juro.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiogenesis Related Markers With Bladder Cancer Outcomes and Other Molecular Markers

Abstract: Angiogenesis related molecular markers are commonly altered in urothelial carcinoma of the bladder, making them a target for therapy. Down-regulation of thrombospondin 1 and up-regulation of basic fibroblast growth factor are independent predictors of clinical outcomes of patients with urothelial carcinoma of the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 23 publications
3
89
1
1
Order By: Relevance
“…The selection process and reasons for exclusion have been summarized in Figure 1. From the 11 studies that were included (Bernardini et al, 2001;Theodoropoulos et al, 2004;Yang et al, 2004;Suzuki et al, 2005;Zu et al, 2006;Herrmann et al, 2007;Nadaoka et al, 2008;Szarvas et al, 2008;Pignot et al, 2009;Shariat et al, 2010;Zaravinos et al, 2012), a total of 1285 patients were analyzed. The characteristics of the selected studies are presented in Table 2.…”
Section: Study Identification and Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The selection process and reasons for exclusion have been summarized in Figure 1. From the 11 studies that were included (Bernardini et al, 2001;Theodoropoulos et al, 2004;Yang et al, 2004;Suzuki et al, 2005;Zu et al, 2006;Herrmann et al, 2007;Nadaoka et al, 2008;Szarvas et al, 2008;Pignot et al, 2009;Shariat et al, 2010;Zaravinos et al, 2012), a total of 1285 patients were analyzed. The characteristics of the selected studies are presented in Table 2.…”
Section: Study Identification and Eligibilitymentioning
confidence: 99%
“…Yu-Jing Huang, Wei-Xiang Qi, Ai-Na He, Yuan-Jue Sun, Zan Shen, Yang Yao* have recently been linked to high levels of VEGF, leading several authors to conclude that an important relationship between VEGF and prognosis exists for bladder cancer (Crew et al, 1997;Inoue et al, 2000;Bernardini et al, 2001;Theodoropoulos et al, 2004;Yang et al, 2004;Zu et al, 2006;Pignot et al, 2009;Shariat et al, 2010;Li et al, 2011). However, conflicting results were showed in other studies regarding the ability of VEGF to predict prognosis in bladder cancer (Suzuki et al, 2005;Nadaoka et al, 2008;Szarvas et al, 2008;Szarvas et al, 2009;Ma et al, 2010;Zaravinos et al, 2012).…”
mentioning
confidence: 99%
“…For example, bladder UC cells produce high levels of vascular endothelial growth factor (VEGF) (12), basic fibroblast growth factor (bFGF) (13), and interleukin-8 (IL-8) (14). These angiogenic factors play important roles in the promotion of angiogenesis and subsequent metastasis (15). Moreover, the expression levels of these factors correlate with tumor stage and disease outcome (6,15).…”
Section: Introductionmentioning
confidence: 99%
“…These angiogenic factors play important roles in the promotion of angiogenesis and subsequent metastasis (15). Moreover, the expression levels of these factors correlate with tumor stage and disease outcome (6,15). As a result, it is hypothesized that inhibiting angiogenesis, either alone or in combination with conventional chemotherapeutics, will improve the outcome in bladder UC patients.…”
Section: Introductionmentioning
confidence: 99%
“…High level of VEGF expression in tumors and in serum samples from patients with UCB also predicted poorer prognosis and increased frequency of disease recurrence (98). Altered VEGF expression has been found to be associated with advanced pathological stage and lymph node metastasis (99). It is suggested that VEGF, in combination with other angiogenic factors such as angiogenin and MMPs, may serve as a biomarker for the diagnosis and prognosis of patients with UCB.…”
Section: Angiogenesismentioning
confidence: 99%